(3x+3).13=78
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a)\(78-3\left(x-1\right)=15\)
\(3\left(x-1\right)=78-15\)
\(3\left(x-1\right)=63\)
\(x-1=63:3\)
\(x-1=21\)
\(x=21+1=22\)
b. \(\left(7x-11\right)^3=2^5.5^2+200\)
\(\left(7x-11\right)^3=32.25+200\)
\(\left(7x-11\right)^3=800+200=1000\)
\(\left(7x-11\right)^3=10^3\)
\(\Rightarrow7x-11=10\)
\(7x=10+11\)
\(7x=21\)
\(x=21:7=3\)
c.\(5.\left(3x-13\right)=5^4\)
\(3x-13=5^4:5\)
\(3x-13=5^3=125\)
\(3x=125+13=138\)
\(x=138:3=46\)
d.\(3.\left(5x-13\right)=3^4\)
\(5x-13=3^4:3=3^3\)
\(5x-13=27\)
\(5x=27+13=40\)
\(x=40:5=8\)
1 ) ( 2x - 15 ) + 17 = 6
=> 2x - 15 = 6 - 17
=> 2x - 15 = - 11
=> 2x = - 11 + 15
=> 2x = 4
=> x = 4: 2
=> x = 2
Vậy x = 2
2) 15 - ( 4 - 3x ) = -4
=> 4 - 3x = 15 - ( -4 )
=> 4 - 3x = 19
=> 3x = 4 - 19
=> 3x = -15
=> x = -15 : 3
=> x = -5
Vậy x = -5
3) -21 + 3 . ( -x + 7 ) = - 18
=> 3 . ( -x + 7 ) = ( -18 ) - ( -21 )
=> 3 . ( -x + 7 ) = 3
=> -x +7 = 3 : 3
=> -x + 7 = 1
=> -x = 1 - 7
=> -x = - 6
=> x = - (- 6 )
Vậy x = - ( -6 )
4 ) 78 : ( 3x - 2 ) = -3
=> 3x - 2 = 78 : ( -3)
=> 3x - 2 = -26
=> 3x = -26 + 2
=> 3x = -24
=> x = -24 : 3
=> x = -8
Vậy x = -8
5) -35 : 5 . ( -3 - 2x ) = 35
=> -7 . ( -3 ) + 2x = 35
=> -3 + 2x = 35 : ( -7)
=> -3 + 2x = -5
=> 2x = (-5) - (-3)
=> 2x = -2
=> x = -2 : 2
=> x = -
Vậy x = -1
~ Chúc bạn học tốt ~
1/ (2x – 15) + 17 = 6
<=> 2x=4
<=> x=2
2/ 15 – (4 – 3x) = - 4
<=> 3x=-15
<=> x=-5
3/ - 21 + 3(-x + 7) = -18
<=> -3x=-18
<=> x=6
4/ 78 : (3x – 2) = -3
<=> 3x-2=-26
<=> 3x=-24
<=> x=-8
5/ -35 : 5.(-3 – 2x) = 35
<=> -3-2x=-7
<=> 2x=4
<=> x=2
Lời giải:
a.
$23+23\times 45+23\times 44=23\times (1+45+44)=23\times 90$
$=23\times (100-10)=23\times 100-23\times 10=2300-230=2070$
b.
$=36\times 280-36\times 79-36$
$=36\times (280-79-1)=36\times (280-80)=36\times 200=7200$
c.
$=72\times 10+72\times 25+72\times 66-72$
$=72\times (10+25+66-1)=72\times 100=7200$
`@` `\text {Ans}`
`\downarrow`
`23 + 23 \times 45 + 23 \times 44`
`= 23 \times (1+45 + 44)`
`= 23 \times 90`
`= 2070`
`b)`
`36 \times 280 - 9 \times 79 \times 4 - 36`
`= 36 \times 280 - 9 \times 4 \times 79 - 36`
`= 36 \times 280 - 36 \times 79 - 36`
`= 36 \times (280 - 79 - 1)`
`= 36 \times 200`
`= 7200`
`c)`
`8 \times 9 \times 10 + 6 \times 25 \times 12 + 4 \times 18 \times 66 - 2 \times 36`
`= 2 \times 4 \times 9 \times 10 + 6 \times 2 \times 6 \times 25 + 2 \times 2 \times 18 \times 66 - 2 \times 36`
`= 10 \times 2 \times 36 + 36 \times 2 \times 25 + 36 \times 2 \times 66 - 2 \times 36`
`= 36 \times 2 \times (10 + 25 + 66 - 1)`
`= 72 \times 100`
`= 7200`
_____
`c)`
`439 \times 78 - 38 \times 78 - 78`
`= 78 \times (439 - 38 - 1)`
`= 78 \times 400`
`= 31200`
`d)`
`24 \times 13 + 6 \times 89 \times 4 - 2 \times 24`
`= 24 \times 13 + 24 \times 89 - 2 \times 24`
`= 24 \times (13 + 89 - 2)`
`= 24 \times 100`
`= 2400`
1, -55 . 78 + ( -13 ) . 78 - 78 . ( -65 )
= 78 . ( -55 - 13 - 65 )
= 78 . ( -133 )
= -10374
Còn lại tự làm
\(1,-55.78+13\cdot\left(-78\right)-78.\left(-65\right)=78\left(-55-13-65\right)=78.\)